Effect of prize draw incentive on the response rate to a postal survey of obstetricians and gynaecologists: A randomised controlled trial. [ISRCTN32823119] - Clark T Justin; Moses Sharon H (BMC, 2004)
Abstract Background Response rates to postal questionnaires are falling and this threatens the external validity of survey findings. We wanted to establish whether the incentive of being entered into a prize draw to win a personal digital assistant (PDA) would increase the response rate for a national survey of consultant obstetricians and gynaecologists. Methods A randomised controlled trial was conducted. This involved sending a postal questionnaire to all Consultant Obstetricians and Gynaecologists in the United Kingdom. Recipients were randomised to receiving a questionnaire offering a prize draw incentive (on response) or no such incentive. Results The response rate for recipients offered the prize incentive was 64% (461/716) and 62% (429/694) in the no incentive group (relative rate of response 1.04, 95% CI 0.96 - 1.13) Conclusion The offer of a prize draw incentive to win a PDA did not significantly increase response rates to a national questionnaire survey of consultant obstetricians and gynaecologists.